Brassica biodiversity conservation: prevailing constraints and future avenues for sustainable distribution of plant genetic resources - Subramanian, Parthiban; Kim, Seong-Hoon; Hahn, Bum-Soo (Frontiers in Plant Science, 2023)
The past decade has seen an observable loss of plant biodiversity which can be attributed to changing climate conditions, destroying ecosystems to create farmlands and continuous selective breeding for limited traits. This loss of biodiversity poses a significant bottleneck to plant biologists across the globe working on sustainable solutions to address the current barriers of agricultural productivity. Plant genetic resources centers or genebanks that conserve plant germplasm can majorly contribute towards addressing this problem. Second only to soybean, Brassica remains the largest oil-seed crop and is cultivated across 124 countries, and FAO estimates for a combined gross production values of broccoli, cabbages, cauliflower, mustard and rape seeds stands at a staggering 67.5 billion US dollars during the year 2020. With such a global status, wide variety of uses and more recently, growing importance in the health food sector, the conservation of diverse genetic resources of Brassica appeals for higher priority.Here we review the current status of Brassica conservation across plant genebanks. At present, at least 81,752 accessions of Brassica are recorded to be conserved in 148 holding institutes spread across only 81 countries. Several aspects that need to be addressed to improve proper conservation of the Brassica diversity was well as dissemination of germplasm are discussed. Primarily, the number of accessions conserved across countries and the diversity of Brassica taxa most countries has been highly limited which may lead to biodiversity loss in the longer run. Moreover, several practical challenges in Brassica germplasm conservation especially with respect to taxonomic authorities have been discussed. The current review identifies and highlights areas for progress in Brassica conservation, which include but are not limited to, distribution of conserved Brassica biodiversity, challenges faced by conservation biologists, conservation methods, technical hurdles and future avenues for research in diverse Brassica species. 1 2 Current Status of Brassica Conservation 2.1 Data collection